(3cJGH aj GdWH GdYdGLjs
(3ChdgG (B:s
(3hgPG LRA def cGf HeYRd Yf GdWH GdbjGSi, jTJed Ydi YdGLGJ HCTQHI heYGLjf hGOgGf eeG jMOK aj GdCHOGf ef GdCeQGV hGdCYQGV s
(3BNQgG (B:s
(3eHJhQ GdBNQ , hBNQ eG ajg(B: (3hbO CYdeJc cja JYbO cd TQGH HgPG GdbGfhf Gdcdi , adG CMJGL Cf CUa dc TQGHkG TQGHG, hdGOgfkG OgfkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B242 - (3U(B269s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B203 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs